INTRINSIC AND EXTRINSIC MOTIVATION IN MAINTAINING CONSISTENCY IN QURAN MEMORIZATION AT NON-FORMAL TAHFIDZ INSTITUTIONS - Zahrani Alawiyah; Amsal Qori Dalimunthe (AL - IBRAH, 2026)
Inconsistent Qur’an memorization among students remains a challenge in non-formal tahfidz institutions, particularly when learning motivation fluctuates. This study examines how intrinsic and extrinsic motivation are implemented and how their interaction sustains memorization consistency. A qualitative case-study design was used at Rumah Tahfidz Miftahul Jannah, Medan. Participants included students, tahfidz teachers, and an administrator, selected purposively due to their direct involvement in memorization activities. Data were collected through semi-structured interviews, observation of halaqah sessions, and institutional documents, and were analyzed through coding, categorization, thematic development, and interactive verification. The findings indicate that spiritual awareness, sincere intention, an understanding of the virtues of memorizing the Qur’an, and personally meaningful goals form the main basis for long-term consistency. External supports including realistic goals, feedback, routine evaluation, recognition, teacher supervision, family involvement, and peer support strengthen discipline and help students maintain a consistent learning rhythm. However, consistency tends to decline when students rely primarily on rewards or supervision and external control is reduced. The study concludes that extrinsic strategies are most effective when they support competence, relatedness, and the gradual internalization of values rather than merely controlling behavior. The findings extend Self-Determination Theory to community-based non-formal tahfidz education and suggest that teachers should progressively transform external reinforcement into autonomous and spiritually grounded motivation.